2019
DOI: 10.3846/ijspm.2019.10429
|View full text |Cite
|
Sign up to set email alerts
|

The Asymmetric Effect of Institutional Quality on Chinese Outward Real Estate Investment

Abstract: Chinese outward investment in real estate (FDIRE) has increased tremendously in recent years. However, it has attracted little attention in the literature. This study aims to assess the asymmetric impact of institutional quality on Chinese outward FDIRE using an extended gravity model with a real estate institutional factor. Using the unique dataset of Chinese outward real estate investment collected from Real Capital Analytics, we identify the main determinants of China’s outward FDIRE. The results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Recognising the uniqueness of the Chinese market (e.g., the imperfections of the Chinese financial market [107] and the high level of air pollution in China), the abovementioned contributions can, to a certain extent, be limited to China. To better understand the variations among the impacts of air quality on property prices globally or in other markets, future studies of air pollution impacts on other housing markets are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Recognising the uniqueness of the Chinese market (e.g., the imperfections of the Chinese financial market [107] and the high level of air pollution in China), the abovementioned contributions can, to a certain extent, be limited to China. To better understand the variations among the impacts of air quality on property prices globally or in other markets, future studies of air pollution impacts on other housing markets are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Sadayuki et al (2019) found that markets with higher transparency have less information asymmetry and attract more inward real estate investment. Furthermore, Zhang et al (2019) also found that transparency impacts foreign real estate investment, but it is conditional on the market size and the country's economic growth. This study, therefore, suggests that the lack of transparency in emerging markets may impact the search cost regardless of the risk-averse strategy of investors (Adair et al , 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…China's outward foreign direct investment (OFDI) has rapidly increased in recent years, with real estate representing one of the fastest-growing sectors. For real estate investment from emerging economies such as China, advanced markets in Australia, Europe, and North America are becoming prime targets in light of favorable market conditions and promising prospects for stable returns (Liang et al, 2019a; Wong, 2017b; Zhang et al, 2019). In the U.S., from 2015 to 2018, Chinese buyers 1 ranked as the top foreign investors in the U.S. real estate market (National Association of Realtors, 2020).…”
Section: Introductionmentioning
confidence: 99%